Correlation Between the Sites of Onset of Basal Cell Carcinoma and the Embryonic Fusion Planes in the Auricle. (December 2018) - Nicoletti, Giovanni; Tresoldi, Marco Mario; Malovini, Alberto; Prigent, Sebastien; Agozzino, Manuela; Faga, Angela
Objectives: This study aims at the identification of the distribution of basal cell carcinomas (BCCs) in the auricle in correlation with the currently most credited sites of the embryonic fusion planes of the auricle. Methods: An overall number of 69 patients with 72 BCCs of the auricle were enrolled in the study over a period of 14 years, from June 2003 to October 2017. All the cases underwent medical preoperative digital photography and the specific location of each BCC was coded on an original full-size anatomical diagram of the auricle derived from the reports by Streeter, Wood-Jones, Park, Porter, and Minoux showing the currently most credited sites of the embryonic fusion planes arbitrarily featured as two 5-mm-wide ribbon-like areas: (1) the hyoid-mandibular fusion plane (HM-FP) running from the upper margin of the tragus toward the concha and then deflecting toward the lower margin of the tragus and (2) the free ear fold-hyoid fusion plane (FEFH-FP) running from the cranial-most portion of the helix to the mid-portion of the ascending helix. The latter fusion planes were comprehensively termed embryological fusion planes (EFP) while all of the remaining surface of the auricle was comprehensively termed non-fusion area (NFA). The surfaces of all of the latter areas were calculated using the ImageJ software. Results: According to our data, the greatest number of BCCs was observed within the currently most credited sites of the embryonic fusion planes of the auricle. The latter sites displayed a 12-fold increased tumor incidence in comparison with the remaining surface of the ear. Conclusions: A correspondence between the sites of onset of BCCs and the sites of merging and/or fusion of embryonal processes was demonstrated in the auricle. Therefore, the latter sites might be considered as high-risk areas for the development of a BCC. Such an evidence provides further support to the hypothesis of an embryological pathogenesis of BCC.